The rare X-ray flaring activity of the ultraluminous X-ray source NGC 4559 X7. Issue 1 (5th April 2021) - Pintore, Fabio; Motta, S; Pinto, C; Bernardini, M G; Rodriguez-Castillo, G; Salvaterra, R; Israel, G L; Esposito, P; Ambrosi, E; Salvaggio, C; Zampieri, L; Wolter, A
ABSTRACT: Ultraluminous X-ray sources are considered amongst the most extremely accreting objects in the local Universe. The recent discoveries of pulsating neutron stars in ULXs strengthened the scenario of highly super-Eddington accretion mechanisms on stellar mass compact objects. In this work, we present the first long-term light curve of the source NGC 4559 X7 using all the available Swift/XRT, XMM–Newton, Chandra, and NuSTAR data. Because of the high quality 2019 XMM–Newton and NuSTAR observations, we investigated in an unprecedented way the spectral and temporal properties of NGC 4559 X7. The source displayed flux variations of up to an order of magnitude and an unusual flaring activity. We modelled the spectra from NGC 4559 X7 with a combination of two thermal components, testing also the addition of a further high energy cut-off power law. We observed a spectral hardening associated with a luminosity increase during the flares, and a spectral softening in the epochs far from the flares. Narrow absorption and emission lines were also found in the RGS spectra, suggesting the presence of an outflow. Furthermore, we measured hard and (weak) soft lags with magnitudes of a few hundreds of seconds whose origin is possibly due to the accretion flow. We interpret the source properties in terms of a super-Eddington accretion scenario assuming the compact object is either a light stellar mass black hole or a neutron star.